The Role of Teachers with Different Educational Backgrounds in the Development of Students’ Learning Motivation - Dahari, Dahari; Utama, Mohamad Maulidin Alif; Rivana, Anggi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
The learning carried out by the teacher in a classroom must develop the qualities of learning, which one of them is students’ learning motivation. Students who are not passionate about learning may find it difficult to develop their achievement. Many students are not aware of the importance of studying seriously. This research was a qualitative research and sampling technique of saturated sample was applied. 30 students were selected as primary data source and 2 teachers was as secondary data source. Data collecting techniques used were in-depth interviews, observation, documentation and questionnaires. The data were analyzed by reducing data, presenting data, drawing conclusions and verification. Research stages I and II involved students and teachers with Da'wah educational background. While, stage III and IV involved students and teachers with PAI educational background.